Effects of lupin-enriched foods on body composition and cardiovascular disease risk factors: a 12-month randomized controlled weight loss trial - Belski, R.; Mori, T.; Puddey, I.; Sipsas, S.; Woodman, R.; Ackland, T.; Dove, E.; Carlyon, N.; Jayasena, Vijay; Hodgson, J.; Beilin, L. (Nature Publishing Group, 2011)
Background: Regular consumption of diets with increased protein or fibre intakes may benefit body weight and composition and cardiovascular disease risk factors. Lupin flour is a novel food ingredient high in protein and fibre.Objective: To investigate the effects of a lupin-enriched diet, during and following energy restriction, on body weight and composition and cardiovascular disease risk factors in overweight individuals.Design: Participants (n=131) were recruited to a 12-month parallel-design trial. They were randomly assigned to consume lupin-enriched foods or matching high-carbohydrate control foods. All participants underwent 3 months of weight loss, 1 month of weight stabilization and 8 months of weight maintenance. Body weight and composition and cardiovascular disease risk factors were assessed at baseline, 4 and 12 months.Results: Lupin, relative to control, did not significantly influence (mean difference (95% CI)) weight loss at 4 months (0.1?kg (-1.2, 1.4)) and 12 months (-0.6?kg (-2.0, 0.8)), maintenance of weight loss from 4 to 12 months (-0.7?kg (-1.83, 0.48)) or measures of body fat and fat-free mass. Relative to control, 24-h ambulatory systolic (-1.3?mm?Hg (-2.4, -0.3), P=0.016) and diastolic (-1.0?mm?Hg (-1.9, -0.2), P=0.021) blood pressures were lower at 12 months but not at 4 months; fasting insulin concentrations and homeostasis model assessment (HOMA) scores were significantly lower at 4 months (-1.2?mU?l–1 (-1.3, -1.1), P=0.004 and -0.6 units (-1.0, -0.19), P=0.004) and 12 months (-1.3 mU?l–1 (-1.4, -1.1), P<0.001 and -0.7 units (-1.1, -0.24), P=0.002).Conclusions: A diet higher in protein and fibre derived from lupin-enriched foods does not enhance weight loss or improve the maintenance of weight loss. However, such a diet may provide cardiovascular health benefits in terms of insulin sensitivity and blood pressure.